STRATEGI PENANGANAN AGENCY PROBLEM PADA PEMBIAYAAN MUDHARABAH DI BMT - MAHMUDATUS SA’DIYAH; NURUL HUDA (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Mudharabah financing is demanded by the transparency of both parties. If one of the parties, especially customers, does not transparently communicate matters related to yield, adverse selection activities can occur and moral hazard is an asymmetric information problem that causes agency problems. Agency problems in mudharabah financing need to be sought to solve the problem so that the owners of capital (shahibul mal / principal) and business actors (mudarib / agents) both benefit in fostering and capturing business partners. This study aims to 1) find out the agency problem that arises in the mudharabah financing scheme in BMT in Jepara Regency, 2) find an effective solution strategy from agency problems in mudharabah financing in BMT in Jepara Regency. This study uses a qualitative approach. Data collection with interviews, observations and documentation. Data analysis techniques use data reduction, data displays and conclusion drawing/verification. Agency The problem that arises in the financing of Mudharobah in the Jepara Regency BMT is that it comes from BMT as an agency, that is, it has not fully utilized management, besides that it is caused by moral standards, financing aspects, technical aspects, and efficiency issues. Effective problem solving strategies of agency problems in Mudharobah financing in BMT in Jepara Regency are project screening, screening mudhorib, compliance with shahibul maal and mundharib on sharia rules in mudaraba contracts.